Dolutegravir versus Placebo in Subjects Harbouring HIV-1 with Integrase Inhibitor Resistance Associated Substitutions: 48-Week Results from VIKING-4, a Randomized Study. Issue 3 (April 2015) - Akil, Bisher; Blick, Gary; Hagins, Debbie P; Ramgopal, Moti N; Richmond, Gary J; Samuel, Rafik M; Givens, Naomi; Vavro, Cindy; Song, Ivy H; Wynne, Brian; Ait-Khaled, Mounir
Background: The Phase III VIKING-3 study demonstrated that dolutegravir (DTG) 50 mg twice daily was efficacious in antiretroviral therapy (ART)-experienced subjects habouring raltegravir- and/or elvitegravir-resistant HIV-1. VIKING-4 (ING116529) included a placebo-controlled 7-day monotherapy phase to demonstrate that short-term antiviral activity was attributable to DTG. Methods: VIKING-4 is a Phase III randomized, double-blind study in therapy-experienced adults with integrase inhibitor (INI)-resistant virus randomized to DTG 50 mg twice daily or placebo while continuing their failing regimen (without raltegravir or elvitegravir) for 7 days (clinicaltrials.gov identifier NCT01568892). At day 8, all subjects switched to open-label DTG 50 mg twice daily and optimized background therapy including ≥1 fully active drug. The primary end point was change from baseline in plasma HIV-1 RNA at day 8. Results: The study population ( n =30) was highly ART-experienced with advanced HIV disease. Patients had extensive baseline resistance to all approved antiretroviral classes. Adjusted mean change in HIV-1 RNA at day 8 was -1.06 log10 copies/ml for the DTG arm and 0.10 log10 copies/ml for the placebo arm (treatment difference -1.16 log10 copies/ml [-1.52, -0.80]; P <0.001). Overall, 47% and 57% of subjects had plasma HIV-1 RNA <50 and <400 copies/ml at week 24, and 40% and 53% at week 48, respectively. No discontinuations due to drug-related adverse events occurred in the study. Conclusions: The observed day 8 antiviral activity in this highly treatment-experienced population with INI-resistant HIV-1 was attributable to DTG. Longer-term efficacy (after considering baseline ART resistance) and safety during the open-label phase were in-line with the results of the larger VIKING-3 study.